Strategi Promosi UPT Perpustakaan UMM pada Masa Pandemi Covid-19 - Puspitasari, Dian (Daluang: Journal of Library and Information Science, 2021)
Introduction: The Covid-19 pandemic caused university libraries to adopt policies restricting small and large-scale activities, including UPT UMM Library. The outbreak required UPT UMM Library to change the routine of library services in normal time by adjusting library services during the pandemic. Therefore, it requires a strategic library promotion.Methodology: The study employed descriptive method with qualitative approach. Data analysis techniques used Cresswell's descriptive qualitative analysis model.Results: The result showed that promotional strategy conducted UMM Library during the Covid-19 pandemic are to create library programs consisting of user education, information literacy classes, seminars and book reviews. In addition, in collaboration with FPPTI of East Java and also FPPTMA, UMM Library created "myUMM Library" which communicates and serves library users though social medias. Conclusion: As a result, the impact generated by the library promotion strategy during the pandemic has significant increase in digital visits and digital access.